THE EXISTENCE OF IDENTITY VALUE AND IMAGE PROTECTION ON LEGAL FRAMEWORKS OF UNITED STATES OF AMERICA (US) AND UNITED KINGDOM (UK) - Hamid, Adnan; Intan, Adilla Meytiara (jfpublisher, 2022)
This research aims to examine the existence of identity value and image protection along with their commercialization by comparing legal frameworks between the United States of America (the US) and the United Kingdom (the UK). The applied methodology is socio-legal approach: Primary sources will be utilized to compare the Right of Publicity’s legal framework in each chosen country, as well as secondary sources, which will be used to develop this author’s understanding of the primary sources, will be crucial to answer the research question. The result of this research stated that The Right of Publicity is a subset of the Right to Privacy specifically guarantee individual to control the commercialization of his identity while providing the remedy for unauthorized commercialization by a third party. English courts and law explicitly dismissed any personality right moreover a general free- standing Right of Publicity. The discussion of the Right of Publicity in the US behaves towards the natural aspect of the right, whether to label the right as property or as personal right. It can be concluded that, The United States approach overprotect the individual’s right to control his identity by banning any commercial use of any characteristics which the public can associate with. On the contrary, the UK still refuse to provide a name to protect the appropriation of one’s identity.